2004
DOI: 10.2174/0929867043364478
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in 4-Thionucleosides as Potential Antiviral and Antitumor Agents

Abstract: The classical 4'-oxonucleoside analogs exhibit interesting biological activities such as antibiotic, antiviral and antitumor, which are believed to be the result of inhibition of the viral or cellular DNA or RNA polymerase after being converted to their corresponding 5'-triphosphates. However, the activity of 4'-oxonucleosides were limited by their susceptibility to degradation by nucleoside phosphorylases or acid hydrolysis. This aspect called for the chemical modification of the carbohydrate portion. This co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(19 citation statements)
references
References 46 publications
0
18
0
1
Order By: Relevance
“…1 H NMR spectra were recorded on 400 MHz instruments in CDCl 3 or DMSO-d 6 with tetramethylsilane as an internal standard. Chemical shifts are reported in parts per million (d), and signals are expressed as s (singlet), d (doublet), t (triplet), m (multiplet), b (broad).…”
Section: Methodsmentioning
confidence: 99%
“…1 H NMR spectra were recorded on 400 MHz instruments in CDCl 3 or DMSO-d 6 with tetramethylsilane as an internal standard. Chemical shifts are reported in parts per million (d), and signals are expressed as s (singlet), d (doublet), t (triplet), m (multiplet), b (broad).…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] Thionucleosides have been studied extensively, [4][5][6][7][8] because of their potent biological activities, 4,5,9 and have been recognized as a novel and important class of antiviral 6,9 and antitumour candidates. [5][6][7][8][9] In recent years, there has been a great deal of activity in the synthesis of fluorine-containing nucleosides and analogues due to the unique properties of the fluorine atom. 10 The promising therapeutic potential of fluoronucleosides along with the unique biological activities of 4 0 -thionucleosides has drawn special attention on the design and synthesis of fluorinated-4 0 -thionucleosides.…”
mentioning
confidence: 99%
“…The IR spectrum of 8 exhibited characteristic absorptions at 1730 (O-acetyl group) and 1685 cm À1 (S-acetyl group). Isopropylidene 8 was then hydrolyzed over 20 min with 90% aqueous TFA at room temperature 24 to give 3-deoxy-3-fluoro-5-S-acetyl-6-O-acetyl-5-thio-D D-glucofuranose (9). Treatment of 9 with methanolic ammonia 25 and direct standard acetylation gave the 5-thioglucopyranose tetraacetate 10, mainly as the a-anomer showing J 1 0 ;2 0 3.2 Hz, J 2 0 ;3 0 10.0 Hz, J 3 0 ;4 0 9.5 Hz in its 1 H NMR spectrum.…”
mentioning
confidence: 99%
“…L-d4C (2b) was found to be and 10-fold more important than that of L-d4C, respectively. Moreover, both compounds were potent inhibitors of cell growth at concentrations below 20 , although L-d4FC did not exhibit any significant mitochondrial DNA inhibition in CEM cells at 100 . Surprisingly, the corresponding Lenantiomer of d4T (2d), which was earlier synthesized by Mansuri et al [28], proved to be inactive.…”
Section: 3 -Unsaturated Nucleosidesmentioning
confidence: 90%
“…As 2 ,3 -didehydro-2 ,3 -dideoxy-2 -fluoronucleosides have exhibited interesting antiviral effects against HIV-1, as well as HBV [42][43][44], it was of interest to report on the synthesis and biological activity of the isosterically substituted 4 -thionucleosides [99,100]. Thus, Chong et al [101] reported the synthesis of -D-2 ,3 -didehydro-2 ,3 -dideoxy-2 -fluoro-4 -thionucleosides 81, 82 (Fig.…”
Section: Thio Unsaturated Nucleosidesmentioning
confidence: 99%